One Health and bioethics: challenges towards integrative medicine - Alarcón Becerra, Jhony Omar (2023)
One Health is an initiative that aims to integrate human, animal and environmental health to better respond to public health challenges; This initiative takes a holistic and ecological perspective to address public health challenges, which involves protecting animal health as an important part of protecting biodiversity and investing in a healthier and more sustainable future. Bioethics appears as the first response to the conflicts derived from the rapid development of scientific knowledge in various fields of medicine and biology, and the verification of environmental damage derived from massive environmental pollution; acts as a balancing element in the concept of One Health, which focuses on the challenges of conflict and violations of human rights and animal protection, offering spaces for debate and facilitating theoretical and practical reflections and decisions regarding the justice, freedom and peace.